Diwali - Dickmann, Nancy (Chicago : Heinemann Library, 2011)
Explains what festivals are, tells the story of Diwali, and looks at how the Hindu holiday is celebrated.
What is a festival? -- The story of Diwali -- Celebrating Diwali today -- Look and see.
Includes index.
School Library Journal
School Library Journal, December 2010
1.7
K-3.
K-3
Keywords: Divali -- Juvenile literature; Festivals -- Juvenile literature; Divali; Festivals; Divali; Festivals; Readers (Elementary).